Dynamic degradation of metallic nanowire networks under electrical stress: a comparison between experiments and simulations. Issue 3 (4th January 2021) - Charvin, Nicolas; Resende, Joao; Papanastasiou, Dorina T.; Muñoz-Rojas, David; Jiménez, Carmen; Nourdine, Ali; Bellet, Daniel; Flandin, Lionel
Abstract : We describe the degradation mechanism in a metallic nanowire network subjected to electrical stress. The nanowire network degradation is ascribed, at a very local scale, to hot-spot formation and the subsequent propagation of a spatially correlated disruptive crack. Abstract : Metallic nanowire networks represent a promising solution for a new generation of transparent and flexible devices, including touch screens, solar cells and transparent heaters. They, however, lack stability under thermal and electrical stresses, often leading to the degradation of nanowires, which results in the loss of electrical percolation paths. We propose a comprehensive description of the degradation mechanism in a metallic nanowire network subjected to electrical stress. The nanowire network degradation is ascribed, at a very local scale, to the hot-spot formation and the subsequent propagation of a spatially correlated disruptive crack. We compare the behaviour of actual networks under electrical and thermal stresses to dynamic simulations of randomly deposited sticks on a 2D surface, and a thermal phenomenon simulated in a metal thin film. On one hand, such comparison allows us to deduce an average junction resistance between nanowires. On the other hand, we observed that initial flaws in a discrete network result in a local current density increase in the surrounding area, further leading to an amplified Joule effect. This phenomenon promotes the spatial correlation in the damage of the percolating network. Such non-reversible failure of the transparent electrode is in good agreement with experimental observations.